Throscidae (Coleoptera) relationships, with descriptions of new fossil genera and species - Muona, Jyrki (Zootaxa, 2019)
Two new Throscidae genera from Baltic amber are described: Tyrannosthroscus n..gen. (type species Tyrannothroscus rex n.sp.) and Pseudothroscus n. gen. (type species Pseudothroscus balticus n. sp.). Four species are described from Baltic amber: Tyrannothroscus rex n. sp., Pseudothroscus balticus n. sp., Potergus superbus n. sp. and Trixagus parvulus n. sp. Pactopus burmensis n. sp. is described from Burmese amber. A phylogenetic analysis of the known throscid genera is performed. Aulonothroscus Horn and Trixagus Kugelann are shown to be sister-groups, the sister-group of this clade is the genus Pactopus Horn and the sister group of these three genera is the genus Potergus Bonvouloir. The oldest previously known throscids were species belonging to the genera Rhomboaspis Kirejtshuk & Kovalev and Potergosoma Kirejtshuk & Kovalev, both from Lebanese Amber, 125–135 Mya. The present analysis shows that the extinct Baltic amber genera Jaira Muona and Pseudothroscus belong to clades at least as old as the Lebanese fossils. The Burmese amber fossil Pactopus burmensis, 99 Mya, is considerably older than any of the previously known species belonging to the four extant genera: Pactopus, Potergus, Aulonothroscus or Trixagus. At least three throscid lineages are now known to have gone extinct. Both the Pactopus and Potergus lineages are more than 99 milion years old, whereas the Aulonothroscus and Trixagus lineages extend at least to the Baltic amber, 50 million years ago. The presence of Jaira in Baltic amber shows that that lineage persisted at least 80 million years before going to extinction.